Combatting Substandard and Falsified Medicines: Public Awareness and Identification of Counterfeit Medications - El-Dahiyat, Faris; Fahelelbom, Khairi M. S.; Jairoun, Ammar Abdulrahman; Al-Hemyari, Sabaa Saleh (Frontiers in Public Health, 2021)
Abstract Objectives: The objective of this study was to determine the identification rate of substandard and falsified medications and its association with knowledge among public. Methods: This cross-sectional study design was conducted in different geographic areas among a random sample of people aged 18 or older. A validated web-based electronic questionnaire was used for data collection tool. The questionnaire contained three sections assessing the following: (1) Sociodemographic data; (2) Knowledge regarding counterfeit medicines; and (3) Ability to identify counterfeit medicines, according to 12 questions rated on a five-point Likert scale. Univariate and multivariate logistic regression analyses were used to assess the association between sociodemographic factors and counterfeit medication identification rate. Results: A total of 320 people participated in the study. Only 98 participants (30.6%, 95% CI 25.6% to 35.7%) identified the counterfeit medications. Ability to correctly identify counterfeit medications was significantly higher in participants who were older (p=0.016), single (p=0.001), Asian (p=0.001), or American (p=0.019), as well as those who indicated that they would check the certification of the medications (p=0.015) and report counterfeit medications to the authorities (p<0.0001). Conclusions: These results underscore the need for greater public awareness of the hazards associated with counterfeit medicines.